A Quasi-Experimental Study: The Influence of Web-Enhanced Learning on Student Learning Independence in the Human Movement System - Nurmuzayyana, Nurmuzayyana; Jamilah, Jamilah; Ola Rivai, Andi Tenri; Rijal, Muhammad (Biosfer: Jurnal Tadris Biologi, 2023)
This study investigates the impact of web-enhanced learning on eighthgrade students' learning independence in the human movement system subject at SMPN Sinjai. Using a nonequivalent control group design, selflearning questionnaires and observation sheets were employed for data collection. Descriptive and inferential analyses included prerequisite tests and independent sample t-tests. Results indicate that students taught with the web-enhanced learning model achieved a high average learning independence score of 124.8, compared to a medium average score of 108.1 for students without this model. The inferential analysis yielded a significance value of tcount 0.000 < 0.05, supporting the rejection of H0 and acceptance of H1. This finding implies a significant influence of webenhanced learning on students' learning independence.ABSTRAK: Penelitian ini menyelidiki pengaruh web-enhanced learning terhadap kemandirian belajar siswa kelas VIII pada mata pelajaran sistem gerak manusia di SMPN Sinjai. Penelitian ini menggunakan non-equivalent control group design, kuesioner kemandiarian belajar, dan lembar observasiuntuk pengumpulan data. Analisis deskriptif dan inferensial dilakukan, termasuk uji prasyarat dan uji t sampel independen. Hasil menunjukkan bahwa siswa yang diajar dengan model pembelajaran web-enhanced mencapai skor kemandirian belajar rata-rata 124,8 (kategori tinggi), dibandingkan siswa yang todak diajar dengan model tersebut dengan skor rata-rata 108,1, kategori sedang. Analisis inferensial menghasilkan nilai signifikansi thitung 0,000 < 0,05, yang berarti H0 ditolakvdan H1 diterima. Hal ini menunjukkan adanya pengaruh yang signifikan dari web-enhanced learning terhadap kemandirian belajar siswa.